Pengaruh Jumlah Nasabah Peminjam Terhadap Perkembangan Aset Badan Usaha Milik Desa (Bumdes) Lestari Di Desa Kumain Kecamatan Tandun Kabupaten Rokan Hulu - risman, risman (Komunitas Manajemen Kompetitif, 2017)
Abstract: Asset development becomes an achievement that should be achieved in a business. BUMDes is a pro-people business entity and provides convenience for the people in obtaining capital. BUMDes assets become a hope in its management, the last few time BUMDes assets have decelerated. On the other hand the number of customers also experienced fluctuations, this study tried to connect the development amount with the development of BUMDes assets. Through quantitative research using secondary data and analyzed by using simple linier regression analysis program with the help of SPSS program obtained the result that the value of t-count = 9.038 is greater than the critical value or shown by t-table of 2.503. then the hypothesis of this study can be accepted and proved that the number of customers significantly affect the development of assets in the State Owned Enterprises (BUMDes) Lestari. Keywords: Increasing Number ff Customers, Development of BUMDes Assets